MO896EMERGENCY HEMODIALYSIS DURING THE CORONAVIRUS PANDEMIC: ABOUT 68 CASES. (29th May 2021) - Chemli, Imen; Amal, Ouni; Haoula, Faouzi; Ben salem, Meriem; Ben salah, Manel; Handous, Insaf; Letaief, Ahmed; Hamouda, Mouna; Aloui, Sabra; Skhiri, Habib
Abstract: Background and Aims: The emergency hemodialysis is a very common situation in nephrology and is characterized by high morbi-mortality. The aim of this work was to determine the indications for emergency hemodialysis, the clinical and paraclinical profiles of the patients, as well as the parameters of the session of hemodialysis and the perdialytic complications. Method: This is a prospective descriptive and analytical study carried out over a period of 3 months (March 3, 2020 - June 6, 2020). This period coincides with the coronavirus pandemic. This study was included all patients who have undergone Emergency hemodialysis. The study was done in the hemodialysis unit of the nephrology department of the CHU Fattouma Bourguiba Monastir. Results: We collected 68 patients, the majority are male (70%). The average age was 60 + -14.4 years. The original department was the emergency room in 42.6% of cases, the intensive care unit in 10.29% and a surgical department in 13.23% of cases. 40% of patients were diabetic and 22% had coronary insufficiency. 60.5% were a chronic renal failure, 16% were end-stage and 34% were on hemodialysis. The indications for emergency hemodialysis were acute lung edema, hyperkalaemia and metabolic acidosis in 31%, 50% and 50% of cases, respectively. Poorly tolerated uremia and anuria more than 12 hours were the indication in 11.8% and 10.3% of cases, respectively, drug or toxic intoxication (methanol) was in 5.9% of cases and hypercalcaemia in 4.4% of cases. The average duration of the sessions was 2.95 hours [2–4 hours]. Ultrafiltration was necessary in 44.11% of cases. Per-dialysis anticoagulation was used in 38.23% of patients. The vascular access was a femoral catheter in 67.6% of cases and an arteriovenous fistula in 28% of cases. The per-dialytic complications were hypotension in 10 cases (14.7%) and the session was stopped in 4 cases. hypoglycemia was noted in 2 cases (2.9%) and seizures in 2 cases. Cardiopulmonary arrest was reported in 2.9% of sessions. The incidence of bleeding complications occurring within 72 hours after the hemodialysis session was 5.8%.The death rate was 13.2%. Our univariate analysis concluded that diabetes, heart failure and coronary artery disease, history of gastrointestinal bleeding and active infection are risk factors for mortality. The multivariate analysis showed that diabetes and a history of gastrointestinal bleeding was the two factors of mortality. Conclusion: The confinement period has affected the medical activity in our department. So, it has increased the cases of emergency hemodialysis with more complications.